Electrochemical Reduction as a Powerful Tool to Highlight the Possible Formation of By-Products More Toxic Than Sudan III Dye - Lizier, Thiago M. [UNESP]; Zanoni, Thalita Boldrin; de Oliveira, Danielle Palma; Zanoni, Maria Valnice Boldrin [UNESP] (Electrochemical Science Group, 2012)
The present work describes the electrochemical reduction of the azo dye Sudan III in methanol/0.01 mol l(-1) Bu4NBF4 at applied potential of -1.2V, which promotes 98% discoloration of the commercial sample. The reduction products were analyzed by high performance liquid chromatography, after optimized conditions for 20 aromatic amines with carcinogenic potentiality. The harmful compounds such as: aniline, benzidine, o-toluidine, 2,6-dimethylaniline, 4,4'-oxydianiline, 4,4'-metileno-bis-2-methylaniline and 4-aminobiphenyl are formed after azo bond cleavage. The electrochemical reduction is compared with chemical reduction by using sodium thiosulfate. Our findings illustrates that commercial Sudan III under reductive condition can forms a number of products, which some are known active genotoxins. The technique could be used to mimic important redox reactions in human metabolism or environment, highlighting the possible formation of by-products more toxic than the original dyes.
Keywords: Aromatic amines; sub products; electrochemical reduction; HPLC; Sudan dyes